2015
DOI: 10.5830/cvja-2015-037
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic heart disease in Africa: is there a role for genetic studies? : review article

Abstract: Rheumatic heart disease (RHD) constitutes a leading cause of premature death and incapacity in Africa, where it is encountered in younger people, and shows a much faster and more malignant course than that seen in Europe or North America. While it is well established that RHD is a consequence of recurrent, untreated group A β-haemolytic streptococcal infections (GAS), the pathogenesis is incompletely understood, and the variation in natural history and phenotypes are not fully explained. In Africa patients are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The detection of genetic susceptibility loci through whole-genome scanning might supply a clinically beneficial genetic risk-prediction marker that will possibly permit an echocardiographic screening and the secondary prophylaxis to point to those at higher risk, thus decreasing the disease burden on the health system of this resource-strained continent [43]. When a hypothetical 2000 birth cohort analysis was done from a societal perspective, the prevention strategy in the form of genetic screening and prophylaxis for high-risk individuals decreased the number of RF patients and elevated the life span at an estimated discounted cost of $7900 per quality-adjusted life-years gained.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of genetic susceptibility loci through whole-genome scanning might supply a clinically beneficial genetic risk-prediction marker that will possibly permit an echocardiographic screening and the secondary prophylaxis to point to those at higher risk, thus decreasing the disease burden on the health system of this resource-strained continent [43]. When a hypothetical 2000 birth cohort analysis was done from a societal perspective, the prevention strategy in the form of genetic screening and prophylaxis for high-risk individuals decreased the number of RF patients and elevated the life span at an estimated discounted cost of $7900 per quality-adjusted life-years gained.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis of several published case-control studies showed a correlation between polymorphisms on several genes encoding for cytokines and predisposition for RHD (103106). Studies in Europe have associated RHD to particular HLA (107109), however, HLA results were inconsistent, and two recent genome-wide association studies (GWAS) conducted in Oceanian populations and European ancestry individuals showed no significance with the risk of developing RHD or ARF, respectively (110, 111). Interestingly, a novel susceptibility signal was identified in the immunoglobulin heavy chain (IGH) locus (110).…”
Section: A High Burden Of Disease Among Indigenous Populations In Thementioning
confidence: 99%
“…This is mainly because there is a wrong assumption that cardiovascular disease is the ailment of the rich and only the developed world. There is also a tendency to associate heart disease mainly with a sedentary lifestyle and hyper nutrition [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%